Impact of laser surface texturing (LST) on the tribological characteristics of piston rings and cylinder liners – a review. Part 2: application of the process. (4th May 2022) - Bathe, R. N.; Padmanabham, G.; Thirumalini, S.; Vaira Vignesh, R.
ABSTRACT: This is the second and final part of a review of the impact of LST on piston rings and cylinder liner tribological characteristics. Part 1 was published in this journal, 2021, 99 (5), 231–237, and traced the development of the laser surface texturing process for materials. Part 2 reviews the development and application of the process to piston-cylinder ring liner contact situations. The future directions for automotive tribological research and desirable areas for research goals related to friction, fuel efficiency, emissions are also discussed. The numbering of figures follows on from those in Part 1, and, like Part 1, the complete reference list is given to enable easy concurrent reading of both parts.